Left ventricular thrombus formation in myocardial infarction is associated with altered left ventricular blood flow energetics. (22nd August 2018) - Garg, Pankaj; van der Geest, Rob J; Swoboda, Peter P; Crandon, Saul; Fent, Graham J; Foley, James R J; Dobson, Laura E; Al Musa, Tarique; Onciul, Sebastian; Vijayan, Sethumadhavan; Chew, Pei G; Brown, Louise A E; et al.
Abstract: Aims: The main aim of this study was to characterize changes in the left ventricular (LV) blood flow kinetic energy (KE) using four-dimensional (4D) flow cardiovascular magnetic resonance imaging (CMR) in patients with myocardial infarction (MI) with/without LV thrombus (LVT). Methods and results: This is a prospective cohort study of 108 subjects [controls = 40, MI patients without LVT (LVT− = 36), and MI patients with LVT (LVT+ = 32)]. All underwent CMR including whole-heart 4D flow. LV blood flow KE wall calculated using the formula:K E = 1 2   ρ b l o o d   .   V v o x e l   .   v 2, where ρ = density, V = volume, v = velocity, and was indexed to LV end-diastolic volume. Patient with MI had significantly lower LV KE components than controls ( P  < 0.05). LVT+ and LVT− patients had comparable infarct size and apical regional wall motion score ( P  > 0.05). The relative drop in A-wave KE from mid-ventricle to apex and the proportion of in-plane KE were higher in patients with LVT+ compared with LVT− (87 ± 9% vs. 78 ± 14%, P  = 0.02; 40 ± 5% vs. 36 ± 7%, P  = 0.04, respectively). The time difference of peak E-wave KE demonstrated a significant rise between the two groups (LVT−: 38 ± 38 ms vs. LVT+: 62 ± 56 ms, P  = 0.04). In logistic-regression, the relative drop in A-wave KE (beta = 11.5, P  = 0.002) demonstrated the strongest association with LVT. Conclusion: Patients with MI have reduced global LV flow KE. Additionally, MI patients with LVT have significantly reduced and delayed wash-in of the LV. The relative drop of distal intra-ventricular A-wave KE, which represents the distal late-diastolic wash-in of the LV, is most strongly associated with the presence of LVT.